A Journey through the Hebrew Scriptures - Frick F. S.; Frick Frank S. (Fort Worth San Diego New York Harcourt Brace College Publishers, 1995)
This text encompasses literary, sociological and gender-related materials, as well as traditional historical methods of criticism. By concentrating on pivotal text from the Hebrew canon and the apocrophyl/deuterocanaonical books, Frick streamlines classroom thought and discussion, leaving room for cultural information from Middle-Eastern archaeology and other sources.
Keywords: 27 (NhRISTIQNSTWOs